Regulatory T cells in peripheral tissue tolerance and diseases - Cheru, Nardos; Hafler, David A.; Sumida, Tomokazu S. (Frontiers in Immunology, 2023)
Maintenance of peripheral tolerance by CD4+Foxp3+ regulatory T cells (Tregs) is essential for regulating autoreactive T cells. Loss of function of Foxp3 leads to autoimmune disease in both animal and in humans with the rare X-linked recessive disorder known as IPEX (Immune dysregulation, polyendocrinopathy, enteropathy X-linked) syndrome. In more common human autoimmune diseases, there are defects in Treg function accompanied with aberrant effector cytokines such as IFN. It has recently become appreciated that Tregs plays an important role in not only maintaining immune homeostasis but also establishing the tissue microenvironment and homeostasis in non-lymphoid tissues. Tissue resident Tregs exert unique profiles that are highly predisposed to tissue environments composed of both immune and non-immune cells in each tissue. Core tissue residence gene signatures are shared across different tissue Tregs and are crucial to maintaining the tissue Treg pool in steady state and are indispensable to homeostatic regulation and maintaining the tissue Treg pool in a steady state. Through interaction with immunocytes and non-immunocytes, tissue Tregs exert suppressive function via conventional ways of both contact dependent and independent manners. In addition, tissue resident Tregs communicate with tissue resident cells to receive signals to fit themselves within a tissue microenvironment where Tregs reside. Those bidirectional interactions are dependent on the tissue type and the nature of the environment to which each tissue is predisposed. Here, we summarize the recent advancements of tissue Treg studies in both human and mice, and discuss the molecular mechanisms that maintain tissue homeostasis and prevent pathogenesis.